The prevalence of anemia and its associated factors among older persons: findings from the National Health and Morbidity Survey (NHMS) 2015 - Krishnapillai, Ambigga Devi; Omar, Mohd Azahadi; Ariaratnam, Suthahar; Awaluddin, S Maria; Sooryanarayana, Rajini; Ho, Bee Kiau; Mohd Tauhid, Noorlaili; Shariff Ghazali, Sazlina (Multidisciplinary Digital Publishing Institute, 2022)
Background: There is limited evidence on the association of anemia with chronic diseases and disabilities among older persons in Malaysia. We assessed the prevalence of anemia and its associated factors among community-dwelling older persons. Methods: This was a cross-sectional study using data from the nationwide National Health and Morbidity Survey 2015 (NHMS 2015) on the health of older adults conducted by the Institute for Public Health, National Institutes of Health, Malaysia. A two-stage stratified random-cluster sampling design was utilized. Data were collected on the sociodemographic profiles, non-communicable disease (NCD) comorbidities (hypertension, diabetes and hypercholesterolemia status) and disabilities among the older persons. Anemia was defined based on the World Health Organization’s standards. A multivariable logistic regression analysis was used to assess the association of anemia with chronic diseases and disabilities. Results: The prevalence of anemia was 35.3% (95% CI: 33.1, 37.4) in the older persons. Chronic disease profiling showed that the prevalence rates of anemia among the older persons with diabetes, hypertension and hypercholesterolemia were 38.6%, 35.3% and 34.1%, respectively. In the multivariable analysis, persons aged 80 years and above (adjusted OR (aOR): 2.64; 95% CI: 2.00, 3.47), 70–79 years (aOR: 1.42; 95% CI: 1.21, 1.66), with diabetes (aOR: 1.30; 95% CI: 1.13, 1.51) and with disabilities in walking (aOR: 1.31; 95% CI: 1.11, 1.54) and self-care (aOR: 1.58; 95% CI: 1.22, 2.05) had higher odds of anemia compared to their respective reference categories. Among the persons with diabetes, the respondents aged 80 years and above (aOR: 2.48; 95% CI: 1.56, 3.94), 70–79 years old (aOR: 1.38; 95% CI: 1.08, 1.76) and with disabilities in vision (aOR: 1.29; 95% CI: 1.02, 1.63) and walking (aOR: 1.50; 95% CI: 1.18, 1.91) were more likely to be anemic. Furthermore, among the older persons without diabetes, persons aged 80 years and above (aOR: 2.89; 95% CI: 2.05, 4.07), 70–79 years old (aOR: 1.46; 95% CI: 1.19, 1.80) and with difficulty in self-care (aOR: 1.87; 95% CI: 1.30, 2.69) were more likely to be anemic. Conclusions: The resilient predictors of developing anemia were advancing age and diabetes, based on our study. Anemia is significantly associated with walking and vision disabilities among older persons with diabetes and with self-care difficulties in those without diabetes. There is a need for future studies to evaluate strategies to prevent anemia among older adults in order to promote healthy aging.